Up for debate! : exploring math through argument - Luzniak, Chris (Stenhouse Publishers, 2020)
"Chris is a math teacher and debate coach, and this book is about how he uses the tools of debate to get his students arguing in math class. Students are highly engaged and learn mathematics more deeply when using his techniques. The book is short and clear and will help readers learn how to incorporate debate in an incremental, totally not overwhelming way because Chris has broken the work down into a lovely step-by-step sequence. It's a super practical and readable manual, written by a working teacher for working teachers"--